2015
DOI: 10.4081/ecj.2015.4781
|View full text |Cite
|
Sign up to set email alerts
|

Complications in critically ill adult patients’ transportations reported in the recent literature

Abstract: The transport of critically ill patients is a complex process, made up by several phases involving the healthcare professionals. It requires a careful planning for the prevention of potential complications undermining the patients' safety outside critical care environment. Literature review about complications and adverse events reported during intra and inter-hospital transport of critically ill adult patients. Intra-hospital transfers are affected by adverse events rates ranging from 22.2 to 75.7% in the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…This shortfall is likely reflected in the high rates of adverse events described in previous studies investigating the transportation of critically ill or injured patients when performed by practitioners who lack advanced or specialised training. [2 , 19 , 20] Importantly, adverse events are often underreported in emergency care and these rates are likely underestimating the true incidence. [21] Our study indicates that there is consistency between the different universities on taught content, and variability between knowledge and skill across the institutions is therefore unlikely to explain such high rates.…”
Section: Discussionmentioning
confidence: 99%
“…This shortfall is likely reflected in the high rates of adverse events described in previous studies investigating the transportation of critically ill or injured patients when performed by practitioners who lack advanced or specialised training. [2 , 19 , 20] Importantly, adverse events are often underreported in emergency care and these rates are likely underestimating the true incidence. [21] Our study indicates that there is consistency between the different universities on taught content, and variability between knowledge and skill across the institutions is therefore unlikely to explain such high rates.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Studies have shown that AEs during CCTs are significant and proportionate to the level of training and experience of the transferring practitioner. [5,6] A literature review in 2015, based on 33 recently published studies on complications during CCTs of adult patients, found that inter-hospital transfers had an AE rate as high as 34%. [5] This appears to be corroborated by a local study among paediatric admissions at a tertiary hospital which showed an AE rate of between 27% and 36%.…”
Section: Discussionmentioning
confidence: 99%
“…[5,6] A literature review in 2015, based on 33 recently published studies on complications during CCTs of adult patients, found that inter-hospital transfers had an AE rate as high as 34%. [5] This appears to be corroborated by a local study among paediatric admissions at a tertiary hospital which showed an AE rate of between 27% and 36%. [7] Further to this, a local paper published as early as 2001 a recommendation that transferring practitioners receive additional training in the care of neonates to avoid in-transit AE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations